Utilization of the Aljazeera Learning Arabic Website to Improve the Listening Skills of Madrasah Aliyah Insan Cendekia Gorontalo Students - Fernando Djafar; Ummi Nadia Rahmah Azzaki (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2026)
This study aims to determine the effectiveness of the Aljazeera Learning Arabic website in improving the listening skills of eleventh-grade students at MAN Insan Cendekia Gorontalo. The research employed a quasi-experimental method with a one-group pretest–posttest design involving 30 students selected through purposive sampling. Data were collected through listening tests, observations, questionnaires, and documentation. The findings showed that the use of the Aljazeera Learning Arabic website had a positive effect on students’ listening abilities. The mean pretest score of 58.90 increased to 76.80 in the posttest. The paired sample t-test result revealed a significance value of 0.000 (p < 0.05), indicating a significant difference between students’ abilities before and after the treatment. In addition to improving listening skills, the website also increased students’ motivation, engagement, and confidence in learning Arabic. Therefore, Aljazeera Learning Arabic is considered an effective digital learning medium for enhancing students’ listening skills in madrasah education.